Subjectivist theories of normative language - Evers, H; Hendrik Willem Adriaan Evers (2011)
On the assumption that there are no objective normative facts, what is the best theory of normative language? I try to answer this question. Chapter 1 argues for a presumption against noncognitivism and explains why error-theories are of limited interest: they concern adverbs and adjectives like ‘moral’, but not words like ‘ought’, ‘good’ and ‘reason’. This narrows down the options: the best subjectivist theory of normative language is a truth conditional, non-error-theoretic account. Chapter 2 argues for contextualism about normative statements. Contextualists hold that their truth conditions (can) vary with the context of utterance. Chapter 3 starts the assessment of contextualist theories. It looks into Humean accounts. Problems are revealed with both Harman’s and Schroeder’s versions. Chapter 4 develops a form of indexical relativism according to which the truth of normative statements depends on contextually salient rules. I present imperative-based analyses of ‘ought’ and ‘reason’ and show how they can explain why ‘A ought to X’ entails that the balance of reasons favours that A X-es. Chapter 5 further develops the theory of chapter 4 and applies it to the words ‘good’ and ‘must’. It turns out to be hard to analyse ‘good’. It also emerges that ‘must’ and ‘ought’ cannot be given different truth conditions. Chapter 6 explains Stephen Finlay’s end-relational theory. On this account, normative statements concern the relation in which acts or objects stand to contextually salient ends. In the case of ‘ought’ and ‘good’, this relation is one of probability raising. Chapter 7 discusses and answers some familiar objections to Finlay’s view. Chapter 8 raises some new problems, related to the fact that normative judgments are often made in the light of several ends. Chapter 9 explains why the end-relational theory is nonetheless the best subjectivist theory of normative language.